Composition and diversity of zooplankton in the surface water of Lake Danao, Ormoc City, Leyte, Philippine from March to July 2021 - Ayon, Lenz Irvin (2022)
Laka Danao is a protected area in Ormoc City, Leyte, and is home to an array of flora and fauna. It also provides several ecosystem services in the area. This study explores the composition and diversity of zooplankton in the lake. Water samples were collected from one meter below surface using 20 microns conical plankton net (qualitative samples) and a wildco alpha sampler (quantitative samples). A total of 14 species from 11 families were recorded from March to July 2021. The month of June has the highest number of recorded zooplankton density at 717.78 indivs/L while the month of July has the lowest at 347.01 indivs/L. Rotifers are the most abundant zooplankton type (82.22%). Similarly, the rotifer family Brachionidae is also the most abundant (59.44%). Keratella cf. Tropica is the most abundant species (56.71%) followed by Polyarthra cf. Vulgaris (13.17%) and the endemic calanoid copepod Filipinodiaptomus vexillifer (11.12%). The highest Shannon-Weiner Diversity Index and Pielou's evenness index is in June (1.709 and 07424, respectively) while the highest Menhinick's Richness Index is recorded in July (0.5368). Temperature, pH, and phosphates are within the range of the water parameter guidelines for Type A water while nitrates and DO are not within the ideal ranges. Canonical Correspondence Analysis shows weak association between the most common species and the environmental factors. The conduct of more sampling efforts in the area is highly encouraged. The possible effects of fish predation on zooplankton could be also looked in the future studies.